2007
DOI: 10.4049/jimmunol.179.9.5748
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Airways Disease Develops after an Increase in Allergen Capture and Processing in the Airway Mucosa

Abstract: Airway mucosal dendritic cells (AMDC) and other airway APCs continuously sample inhaled Ags and regulate the nature of any resulting T cell-mediated immune response. Although immunity develops to harmful pathogens, tolerance arises to nonpathogenic Ags in healthy individuals. This homeostasis is thought to be disrupted in allergic respiratory disorders such as allergic asthma, such that a potentially damaging Th2-biased, CD4+ T cell-mediated inflammatory response develops against intrinsically nonpathogenic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…No studies so far have studied whether lung DC subsets would differentially express any of these enzymes or endocytic targeting receptors. It was shown that mucosal cDC were more endocytic and better at presenting antigenic peptides to naive CD4 1 lymphocytes than lung parenchymal cDC [10,34]. Despite this peptide presentation, only DC matured in vitro or in vivo presented whole protein to T lymphocytes, indicating a mechanism of regulation at the level of antigen processing.…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
“…No studies so far have studied whether lung DC subsets would differentially express any of these enzymes or endocytic targeting receptors. It was shown that mucosal cDC were more endocytic and better at presenting antigenic peptides to naive CD4 1 lymphocytes than lung parenchymal cDC [10,34]. Despite this peptide presentation, only DC matured in vitro or in vivo presented whole protein to T lymphocytes, indicating a mechanism of regulation at the level of antigen processing.…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
“…A number of studies have shown that RTDC within or beneath the airway epithelial cell layer can extend their dendrites through the epithelial junctions, presumably to directly sample the luminal microenvironment (Vermaelen et al, 2001;Jahnsen et al, 2006;Blank et al, 2007;Wikstrom & Stumbles, 2007). We have shown that airway RTDC become activated and up-regulate their capacity to capture and process inhaled allergen prior to the onset of Th2-mediated airways inflammation in mice, suggesting that RTDC play an important early role in the activation and recruitment of Th2 cells to the airways (von Garnier et al, 2007). In addition to the airway epithelium, RTDC subsets are also present in the submucosa and lung parenchyma although subset distribution and turnover rates differ at these sites (Holt et al, 1994;von Garnier et al, 2005).…”
Section: Distribution and Function Of Respiratory Tract Dendritic Cellsmentioning
confidence: 65%
“…In support of the role of DC in the allergic asthmatic response, adoptive transfer of OVA-pulsed DC to naïve mice followed by a respiratory allergen challenge elicited sensitisation and elevated numbers of activated airway OVA-specific CD4 + cells (Lambrecht et al, 2000a,b) . We have demonstrated an increase in the interactions between RTDC and T cells in the airways in rats, and in the activation and allergen-capture status of RTDC in mice, prior to the onset of EAAD and have demonstrated a role for circulating allergen-specific antibody in mediating T cell activation during this response (Huh et al, 2003;von Garnier et al, 2007). Collectively these data suggest that modulation of RTDC function is a key event in the development of EAAD.…”
Section: Respiratory Tract Dendritic Cell In the Development Of Expermentioning
confidence: 70%
See 2 more Smart Citations